Themistocleous, Christos - (:unkn) unknown (My University, 2026)
Hello, I am a BSc (Hons), MSc, PhD and Post-doc graduate of the University of Nottingham (UK) and was appointed Lecturer at Henley Business School, University of Reading (UK) in 2020. Currently, I hold the position of Assistant Professor of Consumer Behaviour and Psychology at the Department of Communication and Marketing, Cyprus University of Technology. My research areas focus on consumer behaviour in matters relating to consumer privacy, physical activity motivators and servicescape research.
Keywords: Consumer behaviour, Marketing, Tourism Studies; business; multidisciplinary